Tantangan Implementasi Sistem Akuntansi pada Startup: Sebuah Pendekatan Studi Kasus - Darmawan, I Made Dwi Hita; Putra, Ida Bagus Ardhi (Universitas Negeri Padang, 2025)
This research discusses the challenges and solutions in the implementation of accounting systems in early stage startups, with a focus on Bali Tech Startup. The main issues identified are reliance on manual or non-integrated methods, financial constraints to adopt accounting software, and limited accounting skills in the startup team. This research aims to identify solutions implemented by startups to overcome these challenges and optimize their accounting systems. The method used is qualitative research with a case study approach. Data was obtained through in-depth interviews with four CEOs of technology startups in Bali. The results show that the solutions implemented include the use of cloud-based accounting applications, intensive training for teams related to accounting and technology basics, and a collaborative approach with mentors or consultants. The novelty of this research lies in its in-depth focus on the challenges and solutions faced by technology startups in Bali. It provides specific insights into technology adaptation and team capacity building in the local context. The conclusion of this study is that the use of cloud-based technology and internal capacity building are crucial for the successful implementation of accounting systems in early-stage startups. Recommendations for future research are to involve a larger sample from various startup sectors, as well as further examine the influence of regulations and other external factors on the implementation of accounting systems in startups.